Need Assessment for the Development of e-Rapor Sehatku as an Adolescents Health Screening Application - Sitoayu, Laras; Dewanti, Lintang Purwara; Melani, Vitira; Agustina, Noni; Fanani, Lutfi (Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
Adolescents are one of the strategic targets for the implementation of health programs. Networking health in adolescents must be fulfilled as the right same health for all Indonesian children. One tool used for screening health is the book Rapor Kesehatanku. This book must own and filled by all students at school. This research aims to analyze the extent to which it is necessary to digitize my health reports to make them more effective and efficient. This research type is a descriptive qualitative study. Study this involving two informants selected key purposively, five informants main and two informants selected supporters with technique snow-ball. Research data was taken with the method of interview depth and FGD. Data analysis was carried out using the content analysis method. From the results, the study can conclude that there must be an E-Rapor Kesehatanku with features including nutritional status checks, growth charts, compliance with TTD consumption, mental health, PTM risk detection, discussion forums, my health e-report reporting, notifications, multiple users (TPG, teachers, students, parents and Health Office) and many educational features contains a short video about adolescent health.